Efficacy Of Tranexamic Acid in Reducing Blood Loss in Primary Total Knee Replacement - Younas, Muhammad Inaamullah; Rauf, Faizan; Mustafa, Muhammad Sheraz; Janjua, Sarmad Nasir; Iqbal, Shaheen; Habib, Khurram (Journal of Rawalpindi Medical College, 2023)
Objective: To determine the efficacy of tranexamic acid in reducing blood loss in primary total knee replacement. Material and Methods: A total of 96 patients having a diagnosis of primary knee osteoarthritis made up the population sample. The Total Knee Replacement patients were separated into two groups. Patients in Group B used Intra venous tranexamic acid, but those in Group A did not use tranexamic acid during the course of the operation or afterwards. Results: Mean age of the patients recorded in group A 63.79±6.60 (years) and in group B 62.96±7.89 (years). The majority of the patients in both groups were females. After surgery, Group B patients who received tranexamic acid reported less blood loss and less haemoglobin reduction as compared to the control group. Conclusion: From our study, we conclude that Tranexamic acid used intravenously during total knee arthroplasty considerably lowers postoperative blood loss.